THE EFFECT OF PLYOMETRIC TRAINING ON SHOOTING ACCURACY AND LIMB MUSCLE STRENGTH OF FOOTBALL ATHLETES AGES 17-27 YEARS OLD IN THE PS PORJAB DHARMASRAYA SITIUNG II - Saputra, Dwi (The Future of Education Journal, 2022)
This research is motivated by the low ability to shoot soccer athletes Ps Porjab. Efforts to overcome these problems require plyometric exercises. This study aims to determine whether plyometric training has an effect on the shooting ability of Ps Porjab soccer athletes. This research is a type of quantitative research using an experimental method approach. While the form of research design used is "one-group pretest-posttest design". The population of this study were all soccer athletes from Ps Porjab who opened up to 15 men. The sample of this study was the soccer athlete Ps Porjab Sittiung II who opened 15 people. The data collection technique used in this study was shooting accuracy and leg muscle strength tests. The data analysis technique used in this research is normality test and hypothesis testing through SPSS 28 at 0.05 level. The results showed that Plyometric exercise gave a good influence on the results of the shooting ability of Ps Porjab soccer athletes, this can be seen from the pretest and posttest hypothesis test scores obtained from Ps Porjab soccer athletes with 0.001 and 0.002 gains. Based on the analysis carried out, obtained a significant value of Plyometric exercise